Cement composite-based rapid repair material under negative temperature environment and preparation method and application thereof
Through the combination of fast hard sulfaluminate cement and ordinary silicate cement and composite auxiliary materials, a rapid repair material of cement composite composite foundation with rapid condensation and high strength under negative temperature environment was developed, and the cement-based repair material was solved. The problems of reduced hydration activity and insufficient adhesion at negative temperatures have achieved rapid repair and high durability, and are suitable for environmental conditions of -5 to -10°C.
Patent Information
- Application Number
- CN202311623131.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The existing cement-based repair materials have reduced hydration activity and slow hardening in negative temperature environments, which cannot meet the needs of rapid repair and opening of traffic, and are prone to cracks and adhesion problems, affecting the durability and safety of the road.
A composite system of fast hard sulfaluminate cement and ordinary silicate cement is adopted, combined with silica fume, quartz sand, polypropylene fiber, glue powder, carbon black, water reducer, lithium carbonate and sodium nitrite, etc., to form high efficiency The cement composite matrix quickly repairs the material to achieve rapid coagulation and high strength, reduce shrinkage and cracks, and enhance adhesion.
It can be quickly repaired and opened to traffic within 2 hours under normal temperature and negative temperature environments. It has excellent durability and crack resistance, reduces maintenance costs, and is suitable for environmental conditions of -5 to -10℃.
Smart Images

Figure CN117843326B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road repair materials, and in particular to a cement composite-based rapid repair material under negative temperature conditions, and a preparation method and application thereof. Background Art
[0002] Most of the pavement layers of roads and bridges in my country are made of asphalt concrete, which has poor tensile deformation resistance. Under the combined effects of temperature difference, shrinkage and vehicle load, the concrete pavement will have different degrees of cracking damage. The appearance of such pavement diseases will, on the one hand, cause harmful ions in rainwater to penetrate into the lower structures such as the reinforced concrete main beam of the bridge through cracks, affecting the service life of the bridge; on the other hand, it will seriously affect the driving comfort and the appearance of the road and bridge deck. Similarly, when the concrete on both sides of the expansion joint of the bridge is impacted, stress concentration is prone to occur and damage is caused. The main forms of expansion joint damage include concrete damage on both sides of the expansion joint and failure of the bond between concrete and steel plate and old concrete, which will cause further damage such as exposure of the steel plate of the expansion joint and fracture of steel bars, which will eventually lead to poor connection between the road surface and the bridge deck, resulting in early damage and affecting traffic operation. Therefore, how to repair the concrete structure at the road and bridge deck and / or expansion joint to extend its service life and service quality is one of the most important problems facing the current public transportation field.
[0003] In response to the above problems, cement-based materials are currently commonly used for repairs. However, with the rapid development of the economy and the accelerated pace of life, the timeliness requirements for concrete structure repair projects are becoming increasingly high, the time required for opening traffic is becoming increasingly shorter, and the durability requirements for repair materials are also becoming increasingly high. At present, the research on rapid repair materials is mainly concentrated in normal temperature environments, but in more than 60% of my country, the winter temperature is below zero, and the negative temperature construction time is as long as 4 months. Therefore, after entering the winter construction period, the cold climate environment causes a significant increase in construction costs and difficulties, and the defects of rapid road repairs are also more prominent and difficult to overcome. Existing cement-based repair materials have the following defects and deficiencies when used:
[0004] 1. Expansion joint repair and bridge deck pavement repair belong to maintenance projects, which require traffic closures, resulting in a reduction in road traffic rates. For highways, the resulting losses are even more serious. Conventional cement concrete materials have a long maintenance cycle and require long road closures, especially in winter environments. The road surface in contact during construction is in a negative temperature state, and the hydration activity of cement-based repair materials is significantly reduced, and the coagulation and hardening are slow, resulting in slow strength development, low final strength, and large shrinkage, which cannot meet the requirements of emergency repair and construction projects to quickly repair and restore traffic in winter.
[0005] 2. The repaired concrete material has a high modulus and is prone to secondary damage under impact load. In addition, there are certain problems with the adhesion between the repair material and the original road surface and expansion joints, which makes the repair material easy to fall off, affecting driving safety.
[0006] 3. Dry shrinkage and thermal shrinkage of cement-based repair materials are one of the main causes of early cracks. Due to the decrease in humidity in the external environment and the water consumption rate generated by the hydration of cement itself being greater than its external water migration rate, negative pressure is generated in the pores, resulting in shrinkage, which ultimately leads to the formation of cracks and the invasion of harmful substances, seriously affecting the durability of concrete. The current conventional repair materials are cement-based materials, which all have dry shrinkage and thermal shrinkage problems.
[0007] At present, the construction projects under negative temperature environment mainly adopt methods such as preheating raw materials and auxiliary insulation heating and curing to increase the material temperature to ensure the normal hydration of cement. However, when carrying out emergency repair and construction work under negative temperature environment, such methods are cumbersome and time-consuming. Therefore, it is of great significance to develop a cement-based rapid repair material that can be normally hydrated and hardened under negative temperature environment. Summary of the invention
[0008] The present invention provides a cement composite-based rapid repair material having fast setting speed, good compatibility and adhesion with base materials, no need for heating maintenance, good construction performance, and excellent durability, which is suitable for rapid repair of road bridge decks / expansion joints at normal temperature and negative temperature, and can meet the requirements of rapid repair and traffic opening within 2 hours under both normal temperature and negative temperature environments, as well as a preparation method and application thereof.
[0009] To achieve the above-mentioned purpose, the present invention provides a cement composite-based rapid repair material for use in a negative temperature environment, comprising: 35-45% of mixed cement and 55-65% of auxiliary materials; wherein the mixed cement comprises: 350-400 parts by weight of fast-hardening sulphoaluminate cement and 18-28 parts by weight of ordinary Portland cement; the auxiliary materials comprise: 20-33 parts by weight of silica fume, 520-580 parts by weight of quartz sand, 1-3 parts by weight of polypropylene fiber, 15-25 parts by weight of rubber powder, 0.5-2.0 parts by weight of carbon black, 2-4 parts by weight of water reducer, 0.2-1.5 parts by weight of lithium carbonate, 0.5-1.0 parts by weight of defoamer, 0.3-1.5 parts by weight of water retainer, 0.1-0.8 parts by weight of expansion agent, 0.2-1.0 parts by weight of nano silicon dioxide, and 0.5-3.5 parts by weight of sodium nitrite.
[0010] The rapid repair material of the present invention comprises a multi-system of fast-hardening sulphoaluminate cement, ordinary silicate cement and silica fume to provide early strength of the material, and utilizes other auxiliary materials to improve its construction performance, improve its flowability and ductility, improve its cohesive strength, increase deformability, and reduce elastic modulus; at the same time, the mixed cement and auxiliary materials can form a good spatial structure, provide excellent durability, and make its construction time meet the requirements of the "Technical Specifications for Maintenance of Highway Cement Concrete Pavement", and can meet the requirements of 2h rapid repair and opening to traffic under normal temperature and negative temperature environment (especially suitable for environmental conditions of -5 to -10°C).
[0011] According to the present invention, the rapid repair material comprises: 37-42% of mixed cement and 58-63% of auxiliary materials; wherein the mixed cement comprises: 355-385 parts by weight of fast-hardening sulphoaluminate cement and 20-25 parts by weight of ordinary Portland cement; the auxiliary materials comprise: 25-30 parts by weight of silica fume, 530-570 parts by weight of quartz sand, 2-3 parts by weight of polypropylene fiber, 15-20 parts by weight of rubber powder, 0.5-1.5 parts by weight of carbon black, 2.5-3.5 parts by weight of water reducing agent, 0.4-1.0 parts by weight of lithium carbonate, 0.3-1.0 parts by weight of defoaming agent, 0.3-1.0 parts by weight of water retaining agent, 0.1-1.0 parts by weight of expansion agent, 0.2-0.5 parts by weight of nano silicon dioxide, and 0.8-2.8 parts by weight of sodium nitrite.
[0012] Various auxiliary materials added to the rapid repair material (such as nano-silicon dioxide, which is an active nanomaterial, can increase the hydration heat release rate, which is beneficial to the coagulation and hardening of the material in a negative temperature environment) can improve the cracking caused by heat release during the cement hydration process, making it more resistant to cracking, thereby extending its service life and improving its durability; at the same time, the material has a fast coagulation speed, rapid strength growth, good compatibility and adhesion with the base material, and can produce a higher bonding strength at an early stage to meet the requirements of rapid repair.
[0013] According to the present invention, the fast-hardening sulphoaluminate cement is R.SAC42.5 or R.SAC52.5; and the ordinary Portland cement is PO42.5 or PO52.5. Ordinary Portland cement has been widely used due to its reliable performance and low price, but it also has problems such as long curing time, slow early strength development, poor fluidity, and low solidification rate. The fast-hardening sulphoaluminate cement not only has the advantages of fast coagulation and hardening, concentrated hydration heat release, and high early strength, but also has good low-temperature hydration and hardening properties, showing the potential for use as a cementitious component in low-temperature or negative temperature environments. By adding ordinary Portland cement to sulphoaluminate cement, the setting time of the mixed cement is effectively reduced, the setting time of the repair material is controllable, and the strength of the mixed cement mortar at various periods is also improved, especially the later strength is greatly improved, meeting the requirements of rapid repair.
[0014] According to the present invention, the particle size of quartz sand is classified into 10-20 mesh, 20-40 mesh, and 70-140 mesh; wherein, the weight of quartz sand of 10-20 mesh is 360-375 parts, the weight of quartz sand of 20-40 mesh is 85-100 parts, and the weight of quartz sand of 70-140 mesh is 85-95 parts. The more reasonable the gradation between different particle sizes of quartz sand, the denser the structure of the rapid repair material. Similarly, the use of quartz sand particles of different particle sizes combined with silica fume can improve the compactness of the microstructure of the rapid repair material, improve the density of the repaired concrete, facilitate the bite and bonding between new and old materials, and improve the mechanical properties and durability of the repaired concrete.
[0015] According to the present invention, the rubber powder is at least one of ethylene-vinyl acetate copolymer rubber powder, acrylic polymer rubber powder, polyethylene oxide rubber powder, styrene-acrylic rubber powder and styrene-butadiene rubber powder.
[0016] Preferably, the rubber powder is ethylene-vinyl acetate copolymer rubber powder.
[0017] According to the present invention, the specific surface area of silica fume is 20000m 2 / kg.
[0018] According to the present invention, the water reducing agent is a polycarboxylic acid high-efficiency water reducing agent. The polycarboxylic acid high-efficiency water reducing agent can disperse cement particles and has a good steric hindrance effect, so that the rapid repair material has the best construction performance.
[0019] According to the present invention, the length specification of the polypropylene fibers is 3 mm, 6 mm or 9 mm.
[0020] Preferably, the length of the polypropylene fiber is 6 mm. Adding polypropylene fiber can improve the anti-cracking performance of the rapid repair material.
[0021] According to the present invention, the water retaining agent is prepared by compounding hydroxypropyl methylcellulose and water absorbing resin in a weight ratio of (0.5-1.5):1.
[0022] Preferably, hydroxypropyl methylcellulose and water-absorbing resin are compounded in a weight ratio of 1: 1. The presence of hydroxypropyl methylcellulose and water-absorbing resin can provide internal curing water to the rapid repair material during repair and maintain the relative humidity inside the cement-based material, which is conducive to alleviating the early self-shrinkage of the rapid repair material and compensating for the rapid shrinkage of concrete, thereby reducing the formation of cracks after repair and enhancing durability.
[0023] According to the present invention, the expansion agent is a compound of a calcium oxide expansion agent and a magnesium oxide expansion agent in a weight ratio of 1: (0.5-1.5).
[0024] Preferably, the calcium oxide expansion agent and the magnesium oxide expansion agent are compounded in a weight ratio of 1: 1. The rapid reaction between the calcium oxide expansion agent and water can compensate for early shrinkage, while the delayed expansion of the magnesium oxide expansion agent is suitable for reducing late shrinkage. The compounded expansion agent can effectively compensate for the early shrinkage of the rapid repair material and reduce the risk of cracking after use.
[0025] According to the present invention, the weight ratio of lithium carbonate to sodium nitrite in the auxiliary material is (0.4-0.6):1. After the lithium carbonate is used in the rapid repair material for repair, the Li + It will form a strong base LiOH, which will increase the alkalinity of cement hydration reaction and accelerate Al 3+ dissolution, thereby promoting the formation of ettringite; Li + It can also destroy the protective film formed during the cement hydration process to shorten the induction period, improve the early hydration degree of the rapid repair material, and the dual effect ultimately shortens the setting time of the mixed cement. Sodium nitrite can reduce the freezing point of the liquid phase in the hydration reaction under negative temperature environment, and there can still be sufficient liquid phase under negative temperature to ensure the continued hydration of cement, so that the amount of hydration product AFt is greatly increased, the hydration degree and rate are greatly improved, and the hydration products overlap each other to form a stable network structure, obtain higher strength, and ensure that the rapid repair material can set and harden normally; at the same time, it can also improve the pore structure of the formed cement stone, reduce large pores and increase small pores (the pores of cement stone with pore diameter greater than 500A without sodium nitrite account for more than 56%, and the pores added with sodium nitrite can be reduced to 47.36%), the ice content is also reduced, and the destructive effect caused by liquid phase freezing is weakened.
[0026] In the present invention, lithium carbonate and sodium nitrite are added to the rapid repair material in a special proportion, and the different ways in which the two components participate in hydration are utilized to ensure that there is sufficient liquid water for the hydration reaction to the greatest extent, thereby promoting the hydration reaction. The two components can also synergistically improve the early hydration of cement minerals, thereby increasing the speed of coagulation and hardening of mixed cement under negative temperature conditions, reducing the coagulation time and improving the early strength, so that the cement composite-based material of the present invention is fully suitable for use in negative temperature environments (especially suitable for environmental conditions of -5 to -10°C), and can meet the engineering requirement of 2h traffic opening.
[0027] The present invention also provides a method for preparing a cement composite-based rapid repair material under a negative temperature environment, comprising the following steps:
[0028] 1) Rapid hardening sulphoaluminate cement, ordinary Portland cement, silica fume, quartz sand, polypropylene fiber, rubber powder, carbon black and water reducing agent are mixed according to weight parts, and stirred at a speed of 120 to 300 r / min for 2 to 5 minutes to obtain component A;
[0029] 2) lithium carbonate, defoamer, water retaining agent, expander, nano silicon dioxide and sodium nitrite are mixed according to weight, and stirred at a rate of 140 to 200 r / min for 2 to 5 minutes to obtain component B;
[0030] 3) Component A and component B are mixed, and stirred at a rate of 100 to 200 r / min for 5 to 10 minutes. After mixing evenly, they are sealed in a moisture-proof packaging bag to obtain the aforementioned cement composite-based rapid repair material under negative temperature environment.
[0031] According to the present invention, the rapid repair material includes: 350-400 parts by weight of fast-hardening sulphoaluminate cement, 18-28 parts by weight of ordinary Portland cement, 20-33 parts by weight of silica fume, 520-580 parts by weight of quartz sand, 1-3 parts by weight of polypropylene fiber, 15-25 parts by weight of rubber powder, 0.5-2.0 parts by weight of carbon black, 2-4 parts by weight of water reducing agent, 0.2-1.5 parts by weight of lithium carbonate, 0.5-1.0 parts by weight of defoaming agent, 0.3-1.5 parts by weight of water retaining agent, 0.1-0.8 parts by weight of expansion agent, 0.2-1.0 parts by weight of nano silicon dioxide, and 0.5-3.5 parts by weight of sodium nitrite.
[0032] The rapid repair material prepared by the present invention controls the hydration reaction process through the coordinated control of various components, so that it can meet the use requirements under normal temperature and negative temperature environments, realize direct mixing, pouring and heating-free maintenance under normal temperature and negative temperature environments, and is suitable for rapid repair of road bridge decks / expansion joints under normal temperature and negative temperature, especially suitable for environmental conditions of -5 to -10°C. It has fast short-term strength improvement and does not affect construction under negative temperature. It is suitable for rapid emergency repairs under negative temperature environments. The repair construction time meets the requirements of the "Technical Specifications for Maintenance of Highway Cement Concrete Pavement", and can meet the requirements of rapid repair and traffic under normal temperature and negative temperature environments.
[0033] In addition, the present invention also provides an application of a cement composite-based rapid repair material in a negative temperature environment in the repair of road and bridge decks and expansion joints. The rapid repair material is the aforementioned cement composite-based rapid repair material in a negative temperature environment; the rapid repair material does not require heating and maintenance in a negative temperature environment and can be opened to traffic for 2 hours.
[0034] The rapid repair material of the present invention can achieve rapid coagulation and hardening and heating-free curing at room temperature and negative temperature, and is particularly suitable for environmental conditions of -5 to -10°C. It has fast early strength development, stable later strength growth, good interface adhesion and fatigue resistance, can be opened to traffic in a short time, has low shrinkage and is not easy to crack, has good durability, reduces maintenance costs, and is more suitable for practical use.
[0035] The cement composite-based rapid repair material under negative temperature environment provided by the present invention can maintain a short setting time under normal temperature and negative temperature environment, and is particularly suitable for environmental conditions of -5 to -10°C. It has fast early strength development, stable later strength growth, good volume stability, a 28-day shrinkage rate of no more than 0.02%, and good crack resistance, impermeability and waterproof performance.
[0036] When the quick repair material of the present invention is used to repair road and bridge decks and expansion joints, the construction is simple and quick. Even in winter construction, no special insulation measures are needed. Heating-free maintenance can be achieved and high mechanical performance can be maintained in a negative temperature environment. The road and bridge deck can be opened to traffic 2 hours after being used to repair the road and bridge deck, which greatly shortens the time for opening to traffic. The material has good practicality, effectively improves the damage resistance of the road and bridge deck and expansion joints, and extends their service life.
[0037] The rapid repair material of the present invention realizes self-compacting molding by combining, proportioning and synergizing various raw materials, utilizing their fluidity and ductility, and exhibits good bonding properties and synergistic force-bearing properties with base materials (such as concrete, stone, and metal), low shrinkage and no cracking, can be constructed at negative temperatures, and can coagulate normally at negative temperatures without being affected in terms of strength growth, so it can be used for road repair without affecting the progress of the project. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 Schematic diagram of the relationship between mass loss rate and freeze-thaw cycle number of different rapid repair materials;
[0040] Figure 2 Schematic diagram of the relationship between the compressive strength loss rate of different rapid repair materials and the number of freeze-thaw cycles. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present invention.
[0042] The following examples use conventional instruments and equipment in the art. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources, and their specifications are conventional specifications in the art. If no specific techniques or conditions are specified in the following examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0043] It should be noted that, in the present invention and the following embodiments, concentrations, ratios, etc. not otherwise specified are all weight concentrations, weight ratios, etc., "%" means weight percentage, and "parts" means parts by weight, which are common writing habits used by those skilled in the art and are therefore not described in detail in the present invention.
[0044] According to the present invention, the application of the rapid repair material comprises the following steps:
[0045] (1) Draw a boundary line on the surface to be repaired according to the damage range, and use a cutting machine to perform boundary cutting along the boundary line to form a pit with a standard geometric shape;
[0046] (2) Remove broken blocks and other debris from the pit and sprinkle water to moisten it;
[0047] (3) Add the cement composite-based rapid repair material into a mixer and stir it at a rate of 50 to 100 r / min for 45 to 60 seconds to evenly disperse it; then add 12 to 15% of water by weight of the rapid repair material and stir it at a rate of 150 to 200 r / min for 100 to 150 seconds to obtain a slurry;
[0048] (4) Pour the slurry into the pit, vibrate and smooth it, and no heating or curing is required.
[0049] According to the present invention, sand or gravel can be added to the slurry in step 3) and stirred evenly to form mortar or concrete for pouring and repairing the potholes. The rapid repair material of the present invention has the characteristics of good fluidity, fast setting time, low elastic modulus, high early strength, high bonding strength, etc., can realize rapid grouting construction, and has good synergistic force with the base layer. The construction is fast and simple, and it can be used for road repair without affecting the progress of the project.
[0050] In order to further improve the performance of the aforementioned rapid repair material, the rapid repair material also includes: 0.5-1 parts by weight of starch acetate and 0.2-1.5 parts by weight of hydroxy calcium phosphate. Starch acetate and hydroxy calcium phosphate work together with other components to form a gel-like structure to fill the internal pores of the rapid repair material, improve the density and integrity of the material, so that it can continuously provide later strength development, and at the same time, it can block and refine the capillaries and prevent water from entering, so that the rapid repair material can significantly reduce the amount of peeling and mass loss rate after freezing and thawing while improving its density, and significantly improve its anti-freeze-thaw effect and anti-freeze performance.
[0051] It should be noted that the defoaming agent in the auxiliary material of the present invention is a powder defoaming agent commonly used in the art, and the water-absorbing resin is a water-absorbing resin commonly used in the art, and no special limitation or redundant description is made.
[0052] It should be noted that the water-absorbing resin used in the examples is polyacrylamide resin, the defoamer is P803 powder defoamer, and the rubber powder is Wacker Chemical 5010N, the strength grade of rapid hardening sulphoaluminate cement is 52.5, and the strength grade of ordinary Portland cement is 42.5.
[0053] The present invention is further described in detail below in conjunction with the examples. However, it should be understood that the examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0054] Embodiment 1:
[0055] A method for preparing a cement composite-based rapid repair material under a negative temperature environment comprises the following steps:
[0056] 1) 374.6 parts by weight of rapid hardening sulphoaluminate cement, 24 parts by weight of ordinary Portland cement, 28 parts by weight of silica fume, 565 parts by weight of quartz sand (including 373 parts of 10-20 mesh, 97 parts of 20-40 mesh, and 95 parts of 70-140 mesh), 3 parts by weight of polypropylene fiber, 22.5 parts by weight of rubber powder, 0.5 parts by weight of carbon black, and 4 parts by weight of water reducing agent were mixed according to weight parts, and stirred at a speed of 180 r / min for 3 minutes to obtain component A;
[0057] 2) 0.4 parts by weight of lithium carbonate, 0.8 parts by weight of a defoamer, 1.2 parts by weight of a water retaining agent, 0.8 parts by weight of a swelling agent, 0.8 parts by weight of nano-silicon dioxide, and 2 parts by weight of sodium nitrite were mixed according to weight, and stirred at a rate of 200 r / min for 5 min to obtain component B;
[0058] 3) Mix component A and component B, and stir them at a constant speed of 200 r / min for 10 minutes. After mixing evenly, seal them in a moisture-proof packaging bag to obtain the rapid repair material.
[0059] The polypropylene fiber has a length of 9 mm. The water retaining agent is a compound of hydroxypropyl methylcellulose and a water-absorbing resin in a weight ratio of 0.5:1. The expansion agent is a compound of a calcium oxide expansion agent and a magnesium oxide expansion agent in a weight ratio of 1:1.5. The weight ratio of lithium carbonate and sodium nitrite in the auxiliary material is 0.4:1.
[0060] Comparative Example 1:
[0061] A method for preparing a cement composite-based rapid repair material under negative temperature environment, which is different from Example 1 in that:
[0062] Step 2) 0.8 parts by weight of a defoamer, 1.2 parts by weight of a water retaining agent, 0.8 parts by weight of a swelling agent, 0.8 parts by weight of nano-silicon dioxide, and 2 parts by weight of sodium nitrite are mixed according to weight parts, and stirred at a rate of 200 r / min for 5 minutes to obtain component B; that is, lithium carbonate is not added to the rapid repair material.
[0063] Comparative Example 2:
[0064] A method for preparing a cement composite-based rapid repair material under negative temperature environment, which is different from Example 1 in that:
[0065] Step 2) 0.4 parts by weight of lithium carbonate, 0.8 parts by weight of defoamer, 1.2 parts by weight of water retainer, 0.8 parts by weight of expander, and 0.8 parts by weight of nano-silicon dioxide are mixed according to weight parts, and stirred at a rate of 200 r / min for 5 minutes to obtain component B; that is, sodium nitrite is not added to the rapid repair material.
[0066] Test Example 1:
[0067] Test method: Add the cement composite-based rapid repair materials of Example 1, Comparative Example 1 and Comparative Example 2 into a mixer, stir at a rate of 100r / min for 45s to evenly disperse them; then add 12% of the weight of the rapid repair material in water, stir at a rate of 200r / min for 100s, pour the obtained slurry into a 40mm×40mm×160mm steel triple test mold, and then put it into a specified curing box for curing. Mixing and molding environment: temperature is 20℃, humidity is ≥50%; curing environment: temperature is 0℃, -5℃, -10℃, humidity: ≥50%. The setting time is measured with reference to GB / T1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency", and 3 parallels are set for each test group to take the average value. The results are shown in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] The results show that when the rapid repair material includes both lithium carbonate and sodium nitrite, sufficient liquid water can be guaranteed to participate in the hydration reaction in a negative temperature environment, thereby promoting the hydration reaction and reducing the rapid coagulation and hardening time of the cement system in a negative temperature state, so that the cement composite-based rapid repair material of the present invention is fully suitable for use in a negative temperature environment.
[0072] Embodiment 2:
[0073] A method for preparing a cement composite-based rapid repair material under a negative temperature environment comprises the following steps:
[0074] 1) 360 parts by weight of rapid hardening sulphoaluminate cement, 25 parts by weight of ordinary Portland cement, 25 parts by weight of silica fume, 565.4 parts by weight of quartz sand (including 373.4 parts of 10-20 mesh, 97 parts of 20-40 mesh, and 95 parts of 70-140 mesh), 2 parts by weight of polypropylene fiber, 16 parts by weight of rubber powder, 1 part by weight of carbon black, and 2.6 parts by weight of water reducing agent were mixed according to weight parts, and stirred at a speed of 150 r / min for 5 minutes to obtain component A;
[0075] 2) 0.6 parts by weight of lithium carbonate, 0.5 parts by weight of defoamer, 0.4 parts by weight of water retaining agent, 0.2 parts by weight of swelling agent, 0.3 parts by weight of nano silicon dioxide, and 1 part by weight of sodium nitrite were mixed according to weight parts, and stirred at a rate of 150 r / min for 5 min to obtain component B;
[0076] 3) Mix component A and component B, and stir them at a constant speed of 150 r / min for 10 minutes. After mixing evenly, seal them in a moisture-proof packaging bag to obtain the rapid repair material.
[0077] The polypropylene fiber has a length of 6 mm. The water retaining agent is a compound of hydroxypropyl methylcellulose and water absorbing resin in a weight ratio of 1:1. The expansion agent is a compound of calcium oxide expansion agent and magnesium oxide expansion agent in a weight ratio of 1:1.
[0078] Embodiment 3:
[0079] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 2 in that the following steps are performed:
[0080] 1) 375 parts by weight of rapid hardening sulphoaluminate cement, 20 parts by weight of ordinary Portland cement, 30 parts by weight of silica fume, 552 parts by weight of quartz sand (including 370 parts of 10-20 mesh, 92 parts of 20-40 mesh, and 90 parts of 70-140 mesh), 2 parts by weight of polypropylene fiber, 17.5 parts by weight of rubber powder, 1 part by weight of carbon black, and 2.9 parts by weight of water reducing agent were mixed according to weight parts, and stirred at a speed of 300 r / min for 2 min to obtain component A;
[0081] 2) 0.75 parts by weight of lithium carbonate, 0.65 parts by weight of a defoamer, 0.75 parts by weight of a water retaining agent, 0.5 parts by weight of a swelling agent, 0.45 parts by weight of nano-silicon dioxide, and 1.5 parts by weight of sodium nitrite were mixed according to weight parts, and stirred at a rate of 200 r / min for 2 min to obtain component B;
[0082] 3) Mix component A and component B, and stir them at a constant speed of 200 r / min for 5 minutes. After mixing evenly, seal them in a moisture-proof packaging bag to obtain the rapid repair material.
[0083] Embodiment 4:
[0084] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 2 in that the following steps are performed:
[0085] 1) 380 parts by weight of rapid hardening sulphoaluminate cement, 25 parts by weight of ordinary Portland cement, 30 parts by weight of silica fume, 533 parts by weight of quartz sand (including 361 parts of 10-20 mesh, 87 parts of 20-40 mesh, and 85 parts of 70-140 mesh), 2 parts by weight of polypropylene fiber, 19.5 parts by weight of rubber powder, 1 part by weight of carbon black, and 3.15 parts by weight of water reducing agent were mixed according to weight parts, and stirred at a speed of 240 r / min for 3 minutes to obtain component A;
[0086] 2) 0.85 parts by weight of lithium carbonate, 0.7 parts by weight of a defoamer, 1.0 parts by weight of a water retaining agent, 0.65 parts by weight of a swelling agent, 0.5 parts by weight of nano-silicon dioxide, and 2.65 parts by weight of sodium nitrite were mixed according to weight parts, and stirred at a rate of 140 r / min for 4 min to obtain component B;
[0087] 3) Mix component A and component B, and stir them at a constant speed of 150 r / min for 7 minutes. After mixing evenly, seal them in a moisture-proof packaging bag to obtain the rapid repair material.
[0088] Comparative Example 3:
[0089] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 2 in that the following steps are performed:
[0090] Step 2) 0.6 parts by weight of lithium carbonate, 0.5 parts by weight of defoamer, 0.4 parts by weight of water retaining agent, 0.2 parts by weight of swelling agent, 0.3 parts by weight of nano silicon dioxide, and 2 parts by weight of sodium nitrite are mixed according to weight parts, and stirred at a rate of 150 r / min for 5 minutes to obtain component B; that is, the weight ratio of lithium carbonate to sodium nitrite in the auxiliary materials is 0.3:1.
[0091] Comparative Example 4:
[0092] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 2 in that the following steps are performed:
[0093] Step 2) 0.96 parts by weight of lithium carbonate, 0.5 parts by weight of defoamer, 0.4 parts by weight of water retaining agent, 0.2 parts by weight of swelling agent, 0.3 parts by weight of nano-silicon dioxide, and 1.2 parts by weight of sodium nitrite are mixed according to weight parts, and stirred at a rate of 150 r / min for 5 minutes to obtain component B; that is, the weight ratio of lithium carbonate to sodium nitrite in the auxiliary materials is 0.8:1.
[0094] Test Example 2:
[0095] Test method: Add the cement composite-based rapid repair materials of Examples 2 to 4 and Comparative Examples 3 and 4 into a mixer, stir at a rate of 100 r / min for 45 seconds to evenly disperse them; then add water and stir at a rate of 200 r / min for 100 seconds, pour the obtained slurry into a 40mm×40mm×160mm steel triple test mold, and then put it into a specified curing box for curing. Stirring and molding environment: temperature is 20°C, humidity is ≥50%; curing environment: humidity: ≥50%.
[0096] The setting time is measured according to GB / T1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency", and the compressive strength is measured according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)"; the fluidity is tested according to GB / T2419-2005 "Test Method for Fluidity of Cement Mortar", and the bonding strength is tested according to JGJ70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", and the base material is a concrete slab that meets the JCT547-2005 "Ceramic Wall and Floor Tile Adhesive" standard. The volume stability is measured according to T0511-2005 "Test Method for Shrinkage of Cement Mortar". The water seepage rate is tested according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", and the elastic modulus is tested according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". Each test group was set up with 3 parallels and the average value was taken. The results are shown in Table 2.
[0097] Table 2
[0098]
[0099]
[0100] The results show that the rapid repair material of the present invention has the characteristics of good fluidity, fast setting time, low elastic modulus, high early strength, stable later strength development, high bonding strength, etc., can realize rapid grouting construction, and the shrinkage rate meets the requirement of "Comparison of Cement Concrete Pavement Slab Repair Materials and Repair Technology" that the 28d shrinkage rate does not exceed 0.02%. Even after curing for 2h in a negative temperature environment, the compressive strength can reach more than 20MPa, which meets the regulations for opening to traffic and is suitable for rapid emergency repairs in a negative temperature environment.
[0101] By comparing the results of Example 2 with Comparative Examples 3 and 4, it is found that adding lithium carbonate and sodium nitrite in a special ratio to the rapid repair material can promote the hydration reaction to the greatest extent, synergistically improve the early hydration of cement minerals, reduce the setting time and improve the early strength, so as to achieve the engineering requirement of 2h opening to traffic.
[0102] Embodiment 5:
[0103] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 2 in that the following steps are performed:
[0104] Step 2) 0.6 parts by weight of lithium carbonate, 0.5 parts by weight of a defoamer, 0.4 parts by weight of a water retaining agent, 0.2 parts by weight of a swelling agent, 0.3 parts by weight of nano-silicon dioxide, 1 part by weight of sodium nitrite, 0.7 parts by weight of starch acetate and 1.2 parts by weight of calcium hydroxyphosphate were mixed according to weight parts, and stirred at a rate of 160 r / min for 4 min to obtain component B.
[0105] Comparative Example 5:
[0106] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 5 in that:
[0107] Step 2) 0.6 parts by weight of lithium carbonate, 0.6 parts by weight of defoamer, 0.8 parts by weight of water retaining agent, 1.0 parts by weight of swelling agent, 0.5 parts by weight of nano silicon dioxide, 1.2 parts by weight of sodium nitrite, and 0.7 parts by weight of starch acetate are mixed according to weight parts, and stirred at a rate of 160 r / min for 4 min to obtain component B.
[0108] Comparative Example 6:
[0109] A method for preparing a cement composite-based rapid repair material under a negative temperature environment, which is different from Example 5 in that the following steps are performed:
[0110] Step 2) 0.6 parts by weight of lithium carbonate, 0.6 parts by weight of defoaming agent, 0.8 parts by weight of water retaining agent, 1.0 parts by weight of swelling agent, 0.5 parts by weight of nano silicon dioxide, 1.2 parts by weight of sodium nitrite and 1.2 parts by weight of calcium hydroxyphosphate were mixed according to weight parts, and stirred at a rate of 160 r / min for 4 min to obtain component B.
[0111] Test Example 3:
[0112] Test method: Add the cement composite-based rapid repair materials of Example 2, Example 5 and Comparative Example 5 and Comparative Example 6 into a mixer, stir at a rate of 100 r / min for 45 seconds to evenly disperse them; then add 14% of the weight of water of the rapid repair material, stir at a rate of 200 r / min for 100 seconds, and pour the obtained slurry into a 40mm×40mm×160mm steel triple test mold, and then put it into the specified curing box for curing. Mixing and molding environment: temperature is 20°C, humidity is ≥50%; curing environment: temperature is -5°C, humidity is ≥50%. Set up 3 parallels for each test group and take the average value. The compressive strength is measured according to the method in Test Example 2.
[0113] Determination of frost resistance: First, each test block was cured in a curing room for 26 days, and then immersed in water for 2 days. Before the freeze-thaw cycle test, the test block was taken out of the water and the surface moisture was wiped off, its mass was weighed and its initial compressive strength was tested. After the initial mass and compressive strength of the test piece were tested after 28 days of curing, the test piece was placed in a KDR-A concrete rapid freeze-thaw tester for freeze-thaw test. The freeze-thaw test method referred to the quick freezing method. During the freezing and thawing process of the test piece, its temperature range was (-18~5)±2℃. The mass and compressive strength of the test piece were tested every 25 freeze-thaw cycles, and the mass loss rate and strength loss rate were used as indicators to evaluate its frost resistance. The number of freeze-thaw cycles was 150. During the freeze-thaw cycle, the test was stopped when the mass loss rate and compressive strength loss rate of the test piece exceeded 5% and 25% respectively. The mass loss rate is the ratio of the mass difference of the test block before and after the freeze-thaw cycle to the mass of the test block before the freeze-thaw cycle. The compressive strength loss rate is the ratio of the compressive strength difference of the test block before and after the freeze-thaw cycle to the compressive strength of the test block before the freeze-thaw cycle. The results are shown in Table 3. Figure 1 , Figure 2 .
[0114] Table 3
[0115] Example 2 Example 5 Comparative Example 5 Comparative Example 6 2h compressive strength MPa 25.4 25.7 25.5 25.1 24h compressive strength MPa 50.5 50.6 50.7 50.4 3d compressive strength MPa 60.9 62.4 61.5 61.2 28d compressive strength MPa 68.7 73.7 70.8 70.3
[0116] The results show that the initial strength of the rapid repair material in Example 5 to which starch acetate and calcium hydroxyphosphate were added was not significantly different from that in Example 2 to which starch acetate and calcium hydroxyphosphate were not added, but the later strength was significantly improved. It can be seen that the two synergistically improved the density and integrity of the material, thereby continuously providing later strength development.
[0117] Figure 1 Schematic diagram of the relationship between the mass loss rate of different rapid repair materials and the number of freeze-thaw cycles.
[0118] Figure 2 Schematic diagram of the relationship between the compressive strength loss rate of different rapid repair materials and the number of freeze-thaw cycles.
[0119] Figure 1 The results show that after 150 freeze-thaw cycles, the mass loss rate of Example 5 is the lowest, which is only 0.64%, which is much lower than 1.33% of Example 2. Although Comparative Examples 5 and 6 are slightly lower than Example 2, the difference is not as significant as that of Example 5. Figure 2 The results show that the compressive strength loss rate of Example 2, Comparative Example 6, and Comparative Example 5 increases slowly in the early stage, and increases faster in the later stage. When the number of freeze-thaw cycles is less than 75 times, the compressive strength loss rate of each group is less than 15%. When the freeze-thaw cycles are greater than 75 times, the compressive strength loss rate of Example 2 and Comparative Example 6 increases sharply, and finally exceeds 25% at the end of the test, while Comparative Example 5 finally reaches 24.3%. The compressive strength loss rate of Example 5 increases relatively slowly, and does not exceed 20% at the end of the test.
[0120] Figure 1 and Figure 2 Both groups of test results show that the mass loss rate and compressive strength loss rate of the rapid repair material in Example 5 are significantly lower than those in Example 2, and show a significant synergistic effect of 1+1>2, indicating that starch acetate and calcium hydroxyphosphate synergistically form a gel-like structure with other components, which fills the pores in the repair material and increases the density of the cement, thereby significantly reducing the compressive strength loss rate and mass loss rate after freeze-thaw, thereby enhancing its ability to resist freeze-thaw cycles and antifreeze performance.
[0121] It should be noted that in the present invention, the detailed steps of some operations are not described in detail, but belong to the prior art known to those skilled in the art, so they will not be repeated here. In addition, in the present invention, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values (including integers and fractions) within the range.
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. In the present invention, not all possible combinations of the various technical features in the various embodiments or embodiments are described. As long as there is no contradiction in the combination of these technical features, the various technical features in the various embodiments or embodiments can be arbitrarily combined, and all possible combinations should be considered to be within the scope of this specification. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cement composite-based rapid repair material for negative temperature environments, characterized in that: include: 35-45% mixed cement and 55-65% auxiliary materials; Wherein, the mixed cement comprises: 350-400 parts by weight of rapid hardening sulphoaluminate cement and 18-28 parts by weight of ordinary Portland cement; The auxiliary materials include: 20-33 parts by weight of silica fume, 520-580 parts by weight of quartz sand, 1-3 parts by weight of polypropylene fiber, 15-25 parts by weight of rubber powder, 0.5-2.0 parts by weight of carbon black, 2-4 parts by weight of water reducing agent, 0.2-1.5 parts by weight of lithium carbonate, 0.5-1.0 parts by weight of defoaming agent, 0.3-1.5 parts by weight of water retaining agent, 0.1-0.8 parts by weight of expansion agent, 0.2-1.0 parts by weight of nano silicon dioxide, and 0.5-3.5 parts by weight of sodium nitrite; The weight ratio of lithium carbonate to sodium nitrite in the auxiliary material is (0.4-0.6):1; The rapid repair material also includes: 0.5 to 1 parts by weight of starch acetate and 0.2 to 1.5 parts by weight of hydroxy calcium phosphate.
2. The cement composite-based rapid repair material for negative temperature environment according to claim 1, characterized in that: The rapid repair material comprises: 37-42% of mixed cement and 58-63% of auxiliary materials; The mixed cement comprises: 355-385 parts by weight of rapid hardening sulphoaluminate cement and 20-25 parts by weight of ordinary Portland cement; The auxiliary materials include: 25-30 parts by weight of silica fume, 530-570 parts by weight of quartz sand, 2-3 parts by weight of polypropylene fiber, 15-20 parts by weight of rubber powder, 0.5-1.5 parts by weight of carbon black, 2.5-3.5 parts by weight of water reducing agent, 0.4-1.0 parts by weight of lithium carbonate, 0.3-1.0 parts by weight of defoaming agent, 0.3-1.0 parts by weight of water retaining agent, 0.1-1.0 parts by weight of expansion agent, 0.2-0.5 parts by weight of nano silicon dioxide, and 0.8-2.8 parts by weight of sodium nitrite.
3. The cement composite-based rapid repair material for negative temperature environment according to claim 1, characterized in that: The rapid hardening sulphoaluminate cement is R.SAC42.5 or R.SAC52.5; the ordinary Portland cement is PO42.5 or PO52.
5.
4. The cement composite-based rapid repair material for negative temperature environment according to claim 1, characterized in that: The particle size of the quartz sand is classified into 10-20 mesh, 20-40 mesh, and 70-140 mesh; among them, the weight portion of the quartz sand of 10-20 mesh is 360-375 parts, the weight portion of the quartz sand of 20-40 mesh is 85-100 parts, and the weight portion of the quartz sand of 70-140 mesh is 85-95 parts.
5. The cement composite-based rapid repair material for negative temperature environment according to claim 1, characterized in that: The rubber powder is at least one of ethylene-vinyl acetate copolymer rubber powder, acrylic polymer rubber powder, polyethylene oxide rubber powder, styrene-acrylic rubber powder and styrene-butadiene rubber powder.
6. The cement composite-based rapid repair material for negative temperature environment according to claim 1, characterized in that: The specific surface area of the silica fume is 20000m 2 / kg; the water reducer is a polycarboxylic acid high-efficiency water reducer; the length specification of the polypropylene fiber is 3mm, 6mm or 9mm; the water retaining agent is a compound of hydroxypropyl methylcellulose and a water-absorbing resin in a weight ratio of (0.5-1.5):1; the expansion agent is a compound of a calcium oxide expansion agent and a magnesium oxide expansion agent in a weight ratio of 1:(0.5-1.5).
7. A method for preparing a cement composite-based rapid repair material under negative temperature environment, characterized in that: The following steps are involved: 1) Rapid hardening sulphoaluminate cement, ordinary Portland cement, silica fume, quartz sand, polypropylene fiber, rubber powder, carbon black and water reducing agent are mixed according to weight parts, and stirred at a speed of 120 to 300 r / min for 2 to 5 minutes to obtain component A; 2) lithium carbonate, defoamer, water retaining agent, expander, nano silicon dioxide, sodium nitrite, starch acetate and calcium hydroxyphosphate are mixed according to weight parts, and stirred at a speed of 140 to 200 r / min for 2 to 5 minutes to obtain component B; 3) Component A and component B are mixed, and stirred at a rate of 100 to 200 r / min for 5 to 10 minutes. After mixing evenly, they are sealed in a moisture-proof packaging bag to obtain the cement composite-based rapid repair material for negative temperature environment according to any one of claims 1 to 6.
8. The method for preparing cement composite-based rapid repair material under negative temperature environment according to claim 7, characterized in that: The rapid repair material includes: 350-400 parts by weight of rapid hardening sulphoaluminate cement, 18-28 parts by weight of ordinary Portland cement, 20-33 parts by weight of silica fume, 520-580 parts by weight of quartz sand, 1-3 parts by weight of polypropylene fiber, 15-25 parts by weight of rubber powder, 0.5-2.0 parts by weight of carbon black, 2-4 parts by weight of water reducing agent, 0.2-1.5 parts by weight of lithium carbonate, 0.5-1.0 parts by weight of defoaming agent, 0.3-1.5 parts by weight of water retaining agent, 0.1-0.8 parts by weight of expansion agent, 0.2-1.0 parts by weight of nano silicon dioxide, 0.5-3.5 parts by weight of sodium nitrite, 0.5-1 parts by weight of starch acetate and 0.2-1.5 parts by weight of calcium hydroxyphosphate.
9. An application of a cement composite-based rapid repair material in repairing road and bridge decks and expansion joints under negative temperature environments, characterized in that: The rapid repair material is the cement composite-based rapid repair material for negative temperature environment as described in any one of claims 1 to 6; the rapid repair material does not require heating and curing in the negative temperature environment and can be opened to traffic for 2 hours.